Assessing The Impact of Record Managers Training on Organizational Performance: A Case Study of Kabale University. - Kyasimiire, Sheillah (Kabale University, 2024)
The study was about the impact of records managers' training on organizational performance. A case study of Kabale University. The study was guided by three objectives which were: to ascertain the impact of records managers' training on organizational performance, to determine the challenges faced by records managers' training on organizational performance, and to suggest possible solutions to records management pieces of training and organizational performance. A total sample of forty-five (45) respondents was considered for the study. This included the Head of Departments, Academic Registrar and University Secretary, and Records Staff. The researcher used both simple random and purposive sampling techniques in identifying the study sample population. The methods that were used in data collection included questionnaires, observation, and interviews. Data collected was edited, coded, entered into the computer, and analyzed with Excel, a Microsoft statistical package, the results were presented in tables. Based on the results from the study all respondents agreed that there were several impacts of records managers training on organizational performances and among others including enhancing the individual's capacity to contribute optimally to the development of the organization, training is an ideal way to learn a job and it helps employees to improve their skills, training is an ideal way to learn a job and it helps employees to improve their skills, employee training programs to improve the adaptability and flexibility of the workforces. From objective two above, it was found out that there was a lack of basic skills and competencies for handling records, technological hurdles because most of the information is kept in the form of multimedia, insufficient cost the record center cannot provide a good service and without good planning on the budget the record, records management are not specific to a particular file format. From the research, objective three it was found as indicated by the respondents from Kabale University that the study findings indicated that employing skilled personnel, maintaining the authenticity and trustworthiness of electronic records, developing a records disaster recovery plan, offering advice to registry organizations, and protection of vital records. The study concluded that the University secretary should appoint a person with a Records Management qualification to revive the records departmental office for effective utilization.